The polychloromethylation/acyloxylation of 1, 6-enynes with chloroalkanes and diacyl peroxides through dual-role designs. Issue 35 (22nd August 2022) - Zhang, Jun-Hao; Jiang, Li-Lin; Hu, Sen-Jie; Li, Jiao-Zhe; Yu, Xuan-Chi; Liu, Fa-Liang; Guan, Yu-Tao; Lei, Ke-Wei; Wei, Wen-Ting
Abstract : The novel polychloromethylation/acyloxylation of 1, 6-enynes with chloroalkanes and diacyl peroxides through dual-role designs has been developed with the use of an inexpensive copper salt under mild conditions. Abstract : The novel polychloromethylation/acyloxylation of 1, 6-enynes with chloroalkanes and diacyl peroxides through dual-role designs has been developed to prepare 2-pyrrolidinone derivatives with polychloromethyl units with the use of an inexpensive copper salt under mild conditions. This strategy includes two dual-role designs, not only improving atomic utilization but also allowing a cleaner process. The wide substrate scope and simple reaction conditions demonstrate the practicability of this protocol.